2021
DOI: 10.1186/s40249-021-00817-4
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial epidemiology of leprosy in northwest Bangladesh: a 20-year retrospective observational study

Abstract: Background Leprosy is known to be unevenly distributed between and within countries. High risk areas or ‘hotspots’ are potential targets for preventive interventions, but the underlying epidemiologic mechanisms that enable hotspots to emerge, are not yet fully understood. In this study, we identified and characterized leprosy hotspots in Bangladesh, a country with one of the highest leprosy endemicity levels globally. Methods We used data from four… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Thus, in a context of controlling spread of the bacillus, correct and early diagnosis and extended surveillance of cured cases and contacts are crucial for reducing the number of new cases and relapse of the disease 3,6,17,22,37,46,76 . The unified treatment (PCT-U) that would waive the need for operational classification, recommended in 2020 by the Ministry of Health in Brazil, is not yet a national or global reality and was not analyzed in this review 62, 63,64,72,78,79 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in a context of controlling spread of the bacillus, correct and early diagnosis and extended surveillance of cured cases and contacts are crucial for reducing the number of new cases and relapse of the disease 3,6,17,22,37,46,76 . The unified treatment (PCT-U) that would waive the need for operational classification, recommended in 2020 by the Ministry of Health in Brazil, is not yet a national or global reality and was not analyzed in this review 62, 63,64,72,78,79 .…”
Section: Discussionmentioning
confidence: 99%
“…Our sensitivity analysis showed that between 21 and 90% of the cases of the next years fall in a defined cluster. This may indicate that in high-endemic areas with a stable leprosy incidence, clusters will remain in the same areas over the next years [ 22 ]. Interventions should therefore be prioritized in these clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Kulldorf 's spatial scan statistic identifies the most likely cluster(s) of cases [20]. The SaTScan [21] has the added value to scan for space-time clustering and is often used in studies to monitor leprosy transmission and clustering over a period [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, communities in resource-limited settings are disproportionately affected by leprosy [ 14 ]. Bangladesh has been considered a high-endemic country for leprosy for many decades, with significant clusters found in the southeast (Cox's Bazar), central regions (around the capital city of Dhaka), and northwest (around Rangpur, Nilphamari, and Saidpur city) [ 15 ]. In 2018 and 2019, approximately four thousand new cases of leprosy were detected each year [ 16 ].…”
Section: Introductionmentioning
confidence: 99%